Anxiety, Depression and Stress in times of pandemic: a study with high school students (Research, Society and Development, 2020)
This papers aims to assess the levels of Anxiety, Depression and Stress of students in the third grade of High School in the midst of the COVID-19 pandemic. The development of the research is anchored in articles of recent literature, and highlights the need for studies that investigate the mental health of students in the process of completing Basic Education. Twenty-one students from a private school, located in the southern half of Rio Grande do Sul, participated in this research. The data collection included the EADs 21 scale (Stress, Anxiety and Depression Scales) and was applied through Google Forms. Through this study it was possible to notice that the students presented indicators of psychological distress, especially Stress. These results represent a worrying warning sign in relation to the adolescents' mental health, since students with a propensity to mental disorder may have their situation even more aggravated in the midst of a pandemic with social isolation and suspension of face-to-face classes.